Peptidomics: methods and strategies - Schrader, Michael; Fricker, Lloyd D. (Methods in molecular biology, 2018)
Origins, Technological Development and Applications of Peptidomics -- Brain Tissue Sample Stabilization and Extraction Strategies for Neuropeptidomics -- Isolation of Endogenous Peptides from Cultured Cell Conditioned Media for Mass Spectrometry -- Mass Spectrometric Identification of Endogenous Peptides -- Bioinformatics for Prohormone and Neuropeptide Discovery -- Substrate Capture Assay using Inactive Oligopeptidases to Identify Novel Peptides -- Non-targeted Identification of d-amino Acid-containing Peptides through Enzymatic Screening, Chiral Amino Acid Analysis and LC-MS -- Quantitative Peptidomics: General Considerations -- Quantitative Peptidomics with Isotopic and Isobaric Tags -- Quantitative Peptidomics using Reductive Methylation of Amines -- Metabolic Labeling to Quantify Drosophila neuropeptides and Peptide Hormones -- Data Preprocessing, Visualization and Statistical Analyses of Non-targeted Peptidomics Data from MALDI-MS -- Affinity Purification of Neuropeptide Precursors from Mice Lacking Carboxypeptidase E Activity -- Mass Spectrometry Based Immunopeptidomics for the Discovery of Cancer Neo-antigens -- Milk Peptidomics to Identify Functional Peptides and for Quality Control of Dairy Products -- Neuropeptidomic Analysis of Zebrafish Brain -- Identification, Quantitation, and Imaging of the Crustacean Peptidome -- Identification of Endogenous Neuropeptides in the Nematode C. elegans using Mass Spectrometry -- EndoProteoFASP as a Tool to Unveil the Peptidome-protease Profile: Application to Salivary Diagnostics -- Methodology for Urine Peptidome Analysis Based on Nano-HPLC coupled to Fourier Transform Ion Cyclotron Resonance Mass Spectrometry -- Identification of Components in Frog Skin Secretions with Therapeutic Potential as Anti-diabetic Agents -- High-Accuracy Mass Spectrometry Based Screening Method for the Discovery of Cysteine Containing Peptides in Animal Venoms and Toxins -- Analysis of the Snake Venom Peptidome -- Identification of Peptides in Spider Venom Using Mass Spectrometry -- Single Cell Peptidomics: Approach for Peptide Identification by N-Terminal Peptide Derivatization -- Peptidomic Identification of Cysteine-Rich Peptides from Plants -- Analysis of Endogenous Peptide Pools of Physcomitrella patens Moss -- The Bright Future of Peptidomics. .
Keywords: Proteomanalyse; Peptide